MODEL ESTIMASI RISIKO PADA PROYEK INFRASTRUKTUR SKEMA KERJASAMA PEMERINTAH DAN SWASTA DENGAN PENDEKATAN FUZZY-DELPHI - Moch Husnullah Pangeran (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
The development of infrastructure under public-private partnerships (PPP) schemes is perceived having a relatively high level of risk. Its referring to the scale of investment which requires generated income to be spread over a long time of concession period. Hence, the success of PPP in infrastructure development can not be separated from the appropriate risks allocation to the involved parties that best able to bear the risks. As one of the key steps in risk management process, risk assessment will provides the profile of the risks identified more depth and specific, then allocated to the parties as the mechanism of risks response. This study develops a model based on fuzzy-delphi approach to facilitate a structured subjective judgement of risks in a PPP infrastructure project. The model was tested by taking the case study of 15 identified major risks in water supply project under PPP concession scheme in Indonesia. The testing and evaluation of the proposed model involves a number of officials and staff from related central government agencies as respondents. By applying Fuzzy-Delphi technique, the probability and impact value of 15 major risks were assessed and quantified. Criteria used for model evaluation are comprehensiveness, clarity, ability to apply in real projects, contribution to the better decision, and overall satisfaction. Evaluation result indicated that the developed model is acceptable according to appreciation and approvals from the respondents representing the parties that are most interested with the model implementation in the future.